Website-based Mail Delivery Scheduling Monitoring System Application at Bappeda, Medan Mayor's Office - Cindy Fricilia; Evpendi; Daniel Daud Sunly Bazikho; Fazar Setiawan; Leni Marlina (Yayasan Sinergi Multidimensi Kreatif, 2024)
The Mail Delivery Scheduling Monitoring System at the Medan Mayor's Office BAPPEDA is a study on the implementation of an information technology system to increase efficiency in the letter delivery process at the Regional Development Planning Agency (BAPPEDA) at the Medan Mayor's Office. This research aims to understand how the use of a mail delivery scheduling monitoring system can optimize time management, increase accuracy, and improve transparency in mail handling in government environments. This study uses a qualitative approach with in-depth interviews and direct observation as data collection methods. The research results show that before the implementation of the mail delivery scheduling monitoring system, the mail delivery process at BAPPEDA tended to be unstructured, time consuming, and prone to errors. However, after the adoption of this system, there was a significant improvement in time management and operational efficiency. System users report improvements in mail tracking, on-time delivery, and real-time monitoring of delivery status. However, several challenges were also identified during system implementation, including resistance to change from some staff, lack of adequate training, and the need for routine maintenance of the system. Thus, this research concludes that although the mail delivery scheduling monitoring system has brought many benefits to BAPPEDA of the Medan Mayor's Office, continued efforts are needed to ensure long-term success and full acceptance by all staff.